Silica nanocomposite based hydrophobic functionality on jute textiles. Issue 3 (4th March 2021) - Ammayappan, Lakshmanan; Chakraborty, Sujay; Pan, Nimai Chandra
Abstract: Cellulosic fibres have hydrophilic property due to the presence of free hydroxyl groups; however, surface functionalization can be used to develop water repellent textiles. Jute is a lignocellulosic fibre and mainly utilised for sacking and hessian due to its stiffness nature. Works on the development of water repellent jute textiles are limited. Work has been carried by applying silica nano sol cum water repellent functional finishing on a bleached jute fabric by pad→dry→cure method. The physical, chemical, morphological, functional, handle and mechanical properties of control and nanocomposite finished jute fabrics were evaluated. Results revealed that silica nanocomposite finished jute fabric has attained the desirable hydrophobic functionality with 138.6 ° water contact angle, 17 ° sliding angle and 10.3 ° water contact angle hysteresis with semi-durable washing durability.